Impact of Netiquette on Email communication - Ramon Bartl (Journal of Applied Leadership and Management, 2017)
Research Question: Does Netiquette in business Email communication have an impact on the recipients' level of understanding, job satisfaction, amount of uncertainty and perception of senders' likability? Does the organizational status of the sender matter and does Netiquette let a negative message sent via Email be evaluated by the recipient lesser negative? Methods: An electronic questionnaire was designed, where the participants (N=105) had to evaluate four sample Emails. Two pretended to be written by a superior and two by a subordinate within the same organization. All Emails delivered a negative message (rejection or criticism). Each pair contained one Email with just the plain message content and one delivered the same message but with common Netiquette cues added respectively. Results: Netiquette significantly improved the understanding and job satisfaction, reduced uncertainty and let the sender appear more favorable. Additionally, the organizational status of the sender resulted in a leveraging positive effect on job satisfaction and the Emails were evaluated less negatively. Evidence for gender differences were also found in the results.
Keywords: 650; Netiquette; Email Communication